Thermal dependence of photo-induced effects in spin-coated As(20)Ge(12.5)S(67.5) thin films - Šlang, Stanislav; Pálka, Karel; Vlček, Miroslav (Elsevier Science BV, 2017)
Chalcogenide glass thin films of ternary As20Ge12.5S67.5 composition were prepared in specular quality using spin-coating technique from n-butylamine based glass solution. The content of organic residuals was notably reduced by post-deposition thermal treatment. The annealing process induced significant structural changes resulting in thin films with the structure close to the source bulk glass. The thickness of deposited thin films was decreasing with increasing annealing temperature. Contrary, the refractive index, optical bandgap, roughness and chemical stability were increasing. The experimental data also proved that deposited thin films were photosensitive as opto-physical properties and chemical resistance were changed after UV light exposure. The exposed thin films annealed bellow 90 degrees C were etched slower than unexposed ones (negative etching) and the thin films annealed above 90 degrees C were etched faster (positive etching).
Teplotní závislost fotoindukovaný jevů v tenkých vrstvách As(20)Ge(12.5)S(67.5) připravených spin-coatingem
Keywords: Chalcogenide glasses; Thin films; Spin-coating; Chalkogenidová skla; Tenké vrstvy; Spin-coating